ACCURACY OF MYKOLAIV ASTEROID OBSERVATIONS WITH DIFFERENT REFERENCE CATALOGUES - Maigurova, N. V.; Pomazan, A. V.; Bodryagin, D. V.; Bondarchuk, L. E. (Одеські астрономічні публікації, 2017)
The results of astrometric reductions of main belt asteroid observations with usage of 3 different reference catalogues are presented. The high precision catalogs CMC15, UCAC4 and GAIA DR1 were used as reference catalogues for calculation asteroid equatorial coordinates. The asteroid observations were carried out at KT-50 telescope of the RI “MAO” Mobitel complex during 2016. The array contains 1666.positions of 68 asteroids mainly in range of (11 – 15) magnitudes. The differences (O – C) were calculated by comparing the obtained topocentric positions with the HORIZONS ephemerides of the JPL laboratory. The mean square errors of the (O – C) values were used for comparison of the different reductions model. The influence of the choice of the reference catalog on the random and systematic asteroid position errors is shown.